Effect of in-situ moisture conservation practices on growth, yield and economics of pearl millet under dryland conditions - SHEKHAWAT, P. S.; KUMAWAT, NARENDRA *; SHEKHAWAT, R .S. (Journal of Soil and Water Conservation, 2021)
Field experiments were conducted on a sandy loam soil at Research Farm, Agricultural Research Station, Bikaner during rainy (kharif) season of 2010-11, 2011-12 and 2012-13 to study the â€œeffect of in-situ moisture conservation practices on growth, yield and economics of pearl millet under dryland conditionsâ€. Data reveals that among the in-situ moisture conservation practices, vegetative mulch at 30 DAS (T5) gave significantly higher growth parameters (plant height, no. of green leaves/plant, total tillers/plant and effective tillers/plant) and yield attributes (ear head length and test weight) of pearlmillet. Similarly, highest grain (2044 kg/ha) and stover yield (3732 kg/ha) was obtained with vegetative much after 30 DAS followed by ridge and furrow at 30 DAS. Maximum gross return (Rs 35016), net return (Rs 27816), B:C ratio (4.86), production efficiency (26.90 kg/ha/day) and economic efficiency (381.04 Rs/ha/day) were also recorded in vegetative mulch at 30 DAS.